Determination of (0,2)-regular sets in graphs and applications - Pacheco, Maria F. (2018)
A (k,tau)- regular set in a graph is a subset of vertices inducing a tau-regular subgraph and such that each vertex not in the set has exactly tau neighbours in it. We will present a new algorithm for the determination of (0, 2)- regular sets as well as its application to the determination of maximum matchings in arbitrary graphs.